The Effect of Using Digital Comic Media on the Excretory System On Students' Digital Elaboration and Literacy Abilities - Rizky Himayanti; Isnaeni, Wiwi (Universitas Negeri Semarang, 2025)
Media is one of the important things needed in learning. The use of learning media in the form of digital comics integrated with PBL is one embodiment of biology learning that is in line with current developments, namely combining science and technology. Digital comics can provide a fun learning experience for students because they are not too difficult to absorb the lesson material. The aim of this research is to determine the effect of digital comic media on excretion system material on students' elaboration and digital literacy abilities. The subjects of this research were students from classes XI-1 to XI-3 at SMA N 1 Mijen Demak. 3 classes were used with 2 classes divided as the experimental group and 1 class as the control group with the number of students XI-1 (34 students), XI-2 (33 students), and XI-3 (34 students). This research was carried out using a quasi-experimental method by giving written tests before and after the research to the experimental and control groups. The instruments used to collect data were questions, LKPD, observation sheets on learning implementation and student activities. Each instrument is used to collect data on students' elaboration abilities (question sheets) and digital literacy (observation sheets and LKPD). This research was analyzed quantitatively (T-test and N-gain) and analyzed qualitatively (observation). The results showed that the experimental class had higher elaboration and digital literacy abilities than the control class. The conclusion of this research is that media digital comics with excretory system material can improve students' elaboration and digital literacy skills and provide new experiences in the biology learning process in the classroom.